ПОЛІЛОГ У СИСТЕМІ ФОРМУВАННЯ КОМУНІКАТИВНОЇ КОМПЕТЕНТНОСТІ МАЙБУТНІХ ФАХІВЦІВ ПОЧАТКОВОЇ ОСВІТИ - БЛЯШЕВСЬКА, А. В.; ДМИТРЕНКО, Н. С.; ФЕДОРЕЦЬ, М. А. (АКАДЕМІЧНІ СТУДІЇ. СЕРІЯ «ГУМАНІТАРНІ НАУКИ», 2023)
The social demand of the Ukrainian society at the present stage is determined that the specialist in the education field should be prepared for the effective performance of their professional functions and full participation in all spheres of life of a multicultural society, which involves the study of the problem on the development of the polylogical communication ability of future teachers. This skill is a necessary reason for successful socialization, full involvement in future professional activities, including the contacts in the international professional spheres. The publication enlightens the importance of polylogue implementation as a form of speech activity (native and foreign), which combines the components of dialogic and monologic speeches during the educational process organization in the higher educational establishment, necessary for the moulding general and professional competencies of the future primary school teacher, respectively to the requirements of legal acts: the Law of Ukraine "On Education", the professional standard for the professions "Teacher of primary classes of a general secondary education institution", "Teacher of primary education (with a diploma of a junior specialist)", State Standard of Primary Education. The work focuses on the usage of the polylogue in the process of implementing the communicative-activity approach in the system of training specialists in primary education field by means of interactive teaching methods, in particular, the debate game, discussion and the project method. The authors substantiate the didactic potential of the polylogue as a synthetic form of speech activities, regarding the achieving the main goal of future teachers’ language learning (native and foreign), which involves effective communication in oral and written language forms, the use of language for the purpose of intercultural communication in the dialogue of cultures and civilizations of the modern world. It has been proven on the basis of the analysis and generalization of the experience of teachers of verbal disciplines in the Municipal Higher Educational Institution “Lutsk Pedagogical College”, in regard to the use of interactive educational technologies, the effectiveness of the project method, educational debate game, in the system of forming general and professional pedagogical competences, primarily native and foreign language communicative competence while teaching students of higher educational institutions in Ukraine.